Charge optimized many body (COMB) potentials for Pt and Au. (28th April 2017) - Antony, A C; Akhade, S A; Lu, Z; Liang, T; Janik, M J; Phillpot, S R; Sinnott, S B
Abstract: Interatomic potentials for Pt and Au are developed within the third generation charge optimized many-body (COMB3) formalism. The potentials are capable of reproducing phase order, lattice constants, and elastic constants of Pt and Au systems as experimentally measured or calculated by density functional theory. We also fit defect formation energies, surface energies and stacking fault energies for Pt and Au metals. The resulting potentials are used to map a 2D contour of the gamma surface and simulate the tensile test of 16-grain polycrystalline Pt and Au structures at 300 K. The stress–strain behaviour is investigated and the primary slip systems {1 1 1}⟨1  1 ¯  0⟩ are identified. In addition, we perform high temperature (1800 K for Au and 2300 K for Pt) molecular dynamics simulations of 30 nm Pt and Au truncated octahedron nanoparticles and examine morphological changes of each particle. We further calculate the activation energy barrier for surface diffusion during simulations of several nanoseconds and report energies of 0.62 ± 0.16 eV for Pt and 1.44 ± 0.06 eV for Au. This initial parameterization and application of the Pt and Au potentials demonstrates a starting point for the extension of these potentials to multicomponent systems within the COMB3 framework.